Geopolitical analysis of the collapse of empires - syrous Ahmadi Nohdani; aziz nasirzade; reyhane salehabadi (تحقیقات کاربردی علوم جغرافیایی)
When empires and great nations decline, there are many interrelated reasons involved in. Empires are considered to be powerful entities in the world, and via historical surveys, one can identify several important empires that have existed in different eras. Geopolitical knowledge and its constituent concepts (power, politics, and space) are closely associated with empires and can be explored from this perspective. The aim of this research is to conduct a geopolitical investigation of the collapse of empires. The research deal with the geopolitical factors contributing to the collapse of empires such as Persia, Rome, Byzantium, Ottoman, Britain, Russia, Spain, and Arab countries, using a descriptive-analytical method and field research. The statistical population consists of 50 specialists and experts in the field of geopolitical studies. The Dimtel method has been utilized to test the conceptual model of the research. The findings demonstrate that variables such as the incompetence and capriciousness of rulers, the collapse of the domestic economy, the extravagance and corruption of the governing class, oppression and slavery, and internal rebellions have a high level of interaction and a strong systemic connection with other variables. In other words, when a country faces these challenges in terms of its leadership and governance, it becomes unable to effectively address other problems caused by these factors, leading to a crisis and the eventual collapse of the empire.